Conjuring the tropical spectres : heavy metal, cultural politics in Singapore and Malaysia - Fu, Kelly (2011)
The evolution of moral panics is dependent on the particular social context and the ability of certain issues to trigger concern within society. In this paper, the authors have employed a cross-comparative study of the heavy metal music subcultures in Singapore and Malaysia to understand the differences in the issues that generate such panics based on the socio-political context of each country and its current concerns. Although the youth involved in both cases are marginalised male Malays, the framing of their alleged deviance and criminality permits, in the case of Singapore, only a limited possibility for moral panic creation given the conservative socio-political governance that limits allegations such as 'Satanism'. In the case of Malaysia, where a 'large-scale' moral panic involving black metal emerged in 2001, the recent trend towards Islamisation gave fodder for the condemnation of black metal based on the allegations of the anti-Islamic behaviour of Muslim youth involved in the black metal scene. In both cases, such groups were exploited by parties claiming to defend the social fabric of the moral majority, but in the latter case it took on grave implications due to the extent of the state and public response. This paper thus argues that the framing of these moral panics is an important component determining the relative 'success' of the panic or its ability to capture public and state imaginings.